Got spirit? The spiritual climate scale, psychometric properties, benchmarking data and future directions. Issue 1 (December 2017) - Doram, Keith; Chadwick, Whitney; Bokovoy, Joni; Profit, Jochen; Sexton, Janel; Sexton, J.
Abstract Background Organizations that encourage the respectful expression of diverse spiritual views have higher productivity and performance, and support employees with greater organizational commitment and job satisfaction. Within healthcare, there is a paucity of studies which define or intervene on the spiritual needs of healthcare workers, or examine the effects of a pro-spirituality environment on teamwork and patient safety. Our objective was to describe a novel survey scale for evaluating spiritual climate in healthcare workers, evaluate its psychometric properties, provide benchmarking data from a large faith-based healthcare system, and investigate relationships between spiritual climate and other predictors of patient safety and job satisfaction. Methods Cross-sectional survey study of US healthcare workers within a large, faith-based health system. Results Seven thousand nine hundred twenty three of 9199 eligible healthcare workers across 325 clinical areas within 16 hospitals completed our survey in 2009 (86% response rate). The spiritual climate scale exhibited good psychometric properties (internal consistency: Cronbach α = .863). On average 68% (SD 17.7) of respondents of a given clinical area expressed good spiritual climate, although assessments varied widely (14 to 100%). Spiritual climate correlated positively with teamwork climate (r  = .434, p  < .001) and safety climate (r  = .489, p  < .001). Healthcare workers reporting good spiritual climate were less likely to have intentions to leave, to be burned out, or to experience disruptive behaviors in their unit and more likely to have participated in executive rounding (p  < .001 for each variable). Conclusions The spiritual climate scale exhibits good psychometric properties, elicits results that vary widely by clinical area, and aligns well with other culture constructs that have been found to correlate with clinical and organizational outcomes.